2002
DOI: 10.1139/x01-186
|View full text |Cite
|
Sign up to set email alerts
|

Wood-density variation of Norway spruce in relation to nutrient optimization and fibre dimensions

Abstract: The effect of fertilization on wood density, fibre length, fibre diameter, lumen diameter, proportion of cell wall area, and cell wall thickness of Norway spruce (Picea abies (L.) Karst.) were studied in a nutrient optimization experiment in northern Sweden. On the fertilized plots, all essential macronutrients and micronutrients were supplied in irrigation water every second day during the growing season. After 12 years' treatment, data were collected from 24 trees (40 years old) on the fertilized and control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
83
2
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 19 publications
14
83
2
7
Order By: Relevance
“…Many authors mentioned that a growth increase might lead to a decrease of wood quality, especially in regard to mechanical properties, those being necessary for wood products used for structural applications (Shmulsky and Jones, 2011). A growth increase can lead to a decrease in wood density (Mâkinen et al, 2002), particularly due to an increase in the number of earlywood cells with nearly no change within the latewood cells (Wang et aL, 2002;Zhang, 1998). However, our results showed a direct relationship between the rate of growth and wood quality for Picea mariana.…”
Section: 3 Wood Qualitycontrasting
confidence: 61%
See 1 more Smart Citation
“…Many authors mentioned that a growth increase might lead to a decrease of wood quality, especially in regard to mechanical properties, those being necessary for wood products used for structural applications (Shmulsky and Jones, 2011). A growth increase can lead to a decrease in wood density (Mâkinen et al, 2002), particularly due to an increase in the number of earlywood cells with nearly no change within the latewood cells (Wang et aL, 2002;Zhang, 1998). However, our results showed a direct relationship between the rate of growth and wood quality for Picea mariana.…”
Section: 3 Wood Qualitycontrasting
confidence: 61%
“…Several European researchers have found that a growth increase can lead to a decrease of wood quality (Mâkinen et aL, 2002;Shmulsky and Jones, 2011), but the relationship between this behavior and specially in black spruce is not described for North America. The knowledge of how wood quality and growth rate are related in this species will lead to optimization of the final products depending on geographical location.…”
Section: Introductionmentioning
confidence: 99%
“…Franceschini et al, 2010). WD in Norway spruce has been shown to present an age-dependent trend from pith to bark (Dutilleul et al, 1998;Hylen, 1999;Mäkinen et al, 2002), apart from the juvenile wood effect. In our study, the juvenile effect was not included for simplicity (series were pruned to exclude the first 3 years) but also because rings near pith anyway are often missing when working with increment cores.…”
Section: Modelling Wood Density For Biomass Incrementmentioning
confidence: 98%
“…The relation between wood density, ring width, and cambial age were proven to fluctuate between trees sampled within a same stand for many species: oak (Guilley et al, 2004;Bergès et al, 2008), common beech (Bouriaud et al, 2004), Norway spruce (Mäkinen et al, 2002;Jaakola et al, 2005;Franceschini et al, 2010). For a given radial growth rate, the trees are building more or less biomass and so storing more or less carbon, according to the density of the wood.…”
Section: Variations Between Treesmentioning
confidence: 99%
“…Extractivefree wood possibly favors char and gas yields during pyrolysis 41 . Furthermore, hardwoods typically have higher densities compared to softwoods, and external factors like silviculture practices can alter density 44 . The main biomass constituent that favors char formation was found to be lignin 41 .…”
Section: Resultsmentioning
confidence: 99%